Differential regulation of transforming growth factor receptors by angiotensin II and transforming growth factor-β1 in vascular smooth muscle - Siegert, Antje; Ritz, Eberhard; Orth, Stefan; Wagner, Jürgen (Journal of molecular medicine, 1999)
Angiotensin II (Ang II) and transforming growth factor (TGF) β1 play a role in vascular remodeling in hypertension. In this process they may interact on various levels, including that of receptor regulation. This consideration prompted the present study on transcriptional regulation of TGF-β receptors by Ang II and TGF-β in vascular smooth muscle cells.
Gesehen am 08.10.2021